Autoimmunity vs. cancer: Predator vs. alien?. (August 2013) - Berens, Christian; Lauber, Kirsten; Herrmann, Martin
<x xml:space="preserve">Abstract</x> "The enemy of my enemy is my friend." According to this motto, the human protagonists in Paul W. S. Anderson's science-fiction movie "Alien vs. Predator" (2004) solidarize with a predator in order to fight the aliens. Can this ancient and simple logic be transferred to the field of oncology and cancer immunotherapy? Can we utilize mechanisms known from the context of autoimmunity to fight cancer? Here, we summarize immune cell-mediated detection of danger and damage, central and peripheral tolerance, immunoregulation and immune privilege — processes known to be deregulated in the context of autoimmunity. We discuss them with special regard towards their misusage by tumors and pathogens and how they might be instrumentalized in the context of anti-cancer immunotherapy.